Uporaba sistema CAD-CAM v protetiki in ortotiki po dvajsetih letih praktičnih izkušenj - Vesenjak, Uroš (Rehabilitacija (Ljubljana), 2022)
The introduction of new and modern technologies and the modernization of technologies in production processes is nowadays a constant. The production of medical devices (MD) is no exception in this respect. The production of MDs is divided into two areas: the serial production of MDs and the production of custom-made MDs for individual users. In this paper, we focus on the latter, more specifically custom-made orthoses and limb prostheses. In the field of prosthetics and orthotics today, the majority of technological processes are a combination of classical and computer-aided processes. At the 13th Days of Rehabilitation Medicine in 2002, an article was published for the first time in Slovenia on the possibilities of using CAD-CAM systems in the field of prosthetics in Slovenia (1). In the current paper, we will present the state of use of modern technological processes in three prosthetics and orthotics workshops in Slovenia. After twenty years, we have gathered and presented our experiences and assessed the advantages and disadvantages that we observe in our work and the use of various modern technological tools and techniques.
Keywords: computer-aided processes; modern technologies; moderne tehnologije; Orthotic Devices; orthotics; ortotika; Prostheses and Implants; prosthetics; protetika; računalniško podprti procesi; rehabilitation; technological tools and techniques; tehnološka orodja in tehnike